2022
DOI: 10.1108/apjml-02-2022-0123
|View full text |Cite|
|
Sign up to set email alerts
|

Purchase intention of organic foods: are lifestyles of health and sustainability the reason for my purchase decision?

Abstract: PurposeThe purpose of this study is to examine the impact of scarcity and the Lifestyles of Health and Sustainability (LOHAS) consumption tendency on the purchase intention of organic foods. The study used the protection motivation theory and the stimulus-organism-response theory to understand the impact of comparatively new variables like “perceived scarcity” and “perceived consumer effectiveness” (PCE) on the consumer's organic food purchase intentions.Design/methodology/approachThe study is using structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…According to Perm (1990), Brunsø et al (2004), Febyanti (2006, Hawkins and Mothersbaugh (2010), Haryono (2015), Alamanda (2018), Romadhoni et al (2015) lifestyle influences the purchasing behaviour of consumers. In the study (Kaur et al, 2022), the authors confirmed that the tendency towards a healthy life and sustainability strongly positively affects the decision to buy organic food. Kim et al (2018), who divided consumers into three food-related lifestyles as the "exploratory consumers", "safety -seeking consumers" and "passive consumers", also contributed to the understanding of the organic food consumption trend.…”
Section: Healthy Lifestyle and Socio-demographic Factorsmentioning
confidence: 60%
“…According to Perm (1990), Brunsø et al (2004), Febyanti (2006, Hawkins and Mothersbaugh (2010), Haryono (2015), Alamanda (2018), Romadhoni et al (2015) lifestyle influences the purchasing behaviour of consumers. In the study (Kaur et al, 2022), the authors confirmed that the tendency towards a healthy life and sustainability strongly positively affects the decision to buy organic food. Kim et al (2018), who divided consumers into three food-related lifestyles as the "exploratory consumers", "safety -seeking consumers" and "passive consumers", also contributed to the understanding of the organic food consumption trend.…”
Section: Healthy Lifestyle and Socio-demographic Factorsmentioning
confidence: 60%
“…In addition, the interpersonal connections get strengthened thereby enhancing the cultural stimulus of the society as culture plays an important role in building the emotions and psychology of the customers. It is, therefore, the sole responsibility of the stakeholders, such as the government, policymakers, budding entrepreneurs and customers to build and increase awareness regarding social literacy through PA, devise policies and awareness programs, provide benefits and incentives for the engagement for better and sustainable development of the society (Kaur et al. , 2022b; Naeem, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The SOR paradigm (Mehrabian and Russell, 1974) is a neo-behavioral technique that describes how individuals strive to treat themselves positively or negatively in response to a particular situation (Kaur et al. , 2022a, b). It also explains the organism’s behavioral responses (R), taking into consideration the effects of external stimuli (S) on interior states (O), which aid in the activation of cognitive or affective systems (Luo et al ., 2020).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic concepts in consumer behavior theory have set down an important basis for the relationship between lifestyle and purchasing decisions for goods and services (Keller & Kotler, 2010;Schiffman et al, 2010). Some recent empirical studies have also revealed many things about the relationship between these two things, both in the case of purchasing goods (Kaur et al, 2022;Matharu et al, 2021;Puteri, Arinda, et al, 2022;Shahid et al, 2022) or services such as financial services (Bananuka et al, 2020;Hassan et al, 2020;Puteri, Parsaulian, et al, 2022). As important as lifestyle is as a consideration in purchasing decisions for goods and services, further effects have been identified on consumptive behavior.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%